Exploring Governance, Political Power, and Democratic Quality in Indonesia: A Qualitative Study - Suhardiman Suhardiman; M. Ibnu Ashari. R.; Fatma Merve Prayogo (Faculty of Social and Political Siences Universitas 17 Agustus 1945 Samarinda, 2026)
Democracy in Indonesia has significantly evolved since the fall of the New Order regime, transitioning to a system that promotes greater participation and freedom. Despite these strides in political reforms, Indonesia's democracy faces challenges, particularly in governance, political power dynamics, and electoral integrity. Political dynasties continue to play a dominant role, concentrating power in a few families, which undermines transparency and accountability in governance. Additionally, the rise of oligarchies, where political and economic elites control decision-making, further distorts democratic processes, limiting true public participation and reinforcing corruption. Elections, while essential for democracy, are often marred by biases within the state apparatus and the influence of money, distorting the representation of the people’s will. This research aims to explore the interplay between political dynasties, oligarchies, and the quality of democracy in Indonesia, focusing on how these factors hinder democratic progress and propose reforms to enhance governance. Utilizing a qualitative research method, the study employed in-depth interviews with political experts, legislators, and academics, supplemented by secondary data from reports and literature. Findings indicate that political dynasties and oligarchies contribute to a lack of transparency and political participation, weakening public trust in democratic institutions. The study recommends reforms in electoral laws, political education, and accountability mechanisms to address these challenges. Strengthening the multi-party system, enhancing the presidential system’s efficiency, and promoting transparency are key to ensuring a more inclusive and functional democracy in Indonesia.